1986
DOI: 10.1021/i300022a036
|View full text |Cite
|
Sign up to set email alerts
|

Gum and deposit formation from jet turbine and diesel fuels at 130.degree.C

Abstract: The ultimate objective of this work is to devise an accelerated test to compare rates of soluble gum and deposit formation from jet turbine and diesel fuels in storage and of hard deposits on hot engine parts. This paper describes rates of oxygen absorption and gum formation in air at 130 "C. For a single fuel or hydrocarbon, the rate of gum formation is closely proportional to the oxygen absorbed, even when this rate varies with purification and additives. In general, pure hydrocarbons absorb oxygen much fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…With the increase of [O 2 ], the peak value of the hydroperoxide number increases significantly, and that of E 75 and E 100 appears 1 h later. Because of the decomposition into free radicals at high temperatures, , the formation rate of hydroperoxides is slower than the decomposition rate when [O 2 ] is low, so the hydroperoxide number decreases. In addition, it can be seen from Figure that the oxidation degree of high [O 2 ] is significantly higher than that of low [O 2 ].…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the increase of [O 2 ], the peak value of the hydroperoxide number increases significantly, and that of E 75 and E 100 appears 1 h later. Because of the decomposition into free radicals at high temperatures, , the formation rate of hydroperoxides is slower than the decomposition rate when [O 2 ] is low, so the hydroperoxide number decreases. In addition, it can be seen from Figure that the oxidation degree of high [O 2 ] is significantly higher than that of low [O 2 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…Mayo et al found that the formation rate of peroxides was related only to time when oxygen pressure was high and related to oxygen content and time when it was low. 23 Moreover, when oxygen pressure increased from 0 to about 0.2 MPa, the amount of gum increased by about 40 times. 24 For improving the oxidation stability of endothermic hydrocarbon fuels, the oxygen content needs to be reduced to 1 ppm level so that the decomposition mechanism is no longer important.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Gum refers to the resinous, non-volatile, high molecular weight polymeric material formed in fuels in storage or when exposed to high temperature conditions during combustion in engines [1]. Gum formation and inhibition in refined petroleum products such as gasoline, diesel and aviation fuel has been extensively studied as a result of its impact on product storability and engine performance but similar studies on gas condensates are scarce [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Lauer et al (1985) analyzed jet fueld deposits by using FTIR and suggested a two-stage deposit formation process: an early stage where the deposits 0888-5885/90/2629-1954$02.50/0 formed are rich in hydroperoxide and epoxide groups and a later stage where the deposits originate from highly oxidized hydrocarbon species and are rich in ketone and ester groups. Mayo and Lan (1986) proposed that fuel-derived deposits originate from soluble gum and that agitation of oxidation flasks may cause deposition of deposit films on the walls instead of deposit sediments. Hazel et al (1986) in an Auger electron spectroscopy (AES)/depth-profiling study of deposits from aviation kerosene on aluminum surfaces found that segregation of Mg from the bulk of the aluminum to its surface oxide and the flow dynamics of the test reduced the formation of deposits.…”
Section: Introductionmentioning
confidence: 99%